Laporan Kasus: Tatalaksana Median Rhomboid Glossitis Pada Pasien Usia Lanjut - Ginanjar Hidayatullah; Ayu Mashartini Prihanti (Fakultas Kedokteran Gigi Universitas Jember, 2018)
Median Rhomboid Glossitis (MRG) is papilla atrophy in the middle portion of the tongue which occurs in 0.01% - 0.1% of the population. Median Rhomboid Glossitis is believed to be a disorder of the development of tongue formation that occurs in the middle of the dorsum surface of the tongue at the 2/3 anterior linkage with 1/3 posterior tongue. The depapillated area is a persistent impregnated tubercle and cannot fully integrate with the lateral lingual in the development of the tongue. Research shows various predisposing factors associated with MRG such as wearing dentures, smoking, diabetes mellitus, and Candida fungal infections. The purpose of this paper was to report the management of MRG cases in elderly patients. 57-year-old male patient came to the Oral Medicine Department RSGM UNEJ with complaints of painful tongue, intraoral clinical features in the dorsum of the tongue found atrophy of papillae, rhomboid, erythema, round shape with a diameter of ± 2 cm. The patient's final diagnosis is Median Rhomboid Glossitis with involvement of Candida infection which is established from subjective, objective examination and mycological investigations. Therapy in such cases is to provide topical nystatin antifungal drugs and multivitamins with B complex and zinc content. MRG patients with Candida infection involvement give positive results in topical nystatin antifungal therapy.